Sweet Syndrome and Secondary Syphilis in a Person with Acute Necrotizing Tonsillitis - Joseph Mishal; Igor Viner; Alexandro Livoff; Shlomo Maayan; Eli Magen (Karger Publishers, 2021)
Syphilis has received its classical designation as one of "the great imitators," reflecting a wide variety of symptoms and presentations, which can cause difficulties in diagnosis. Here we report an unusual case of secondary syphilis in a person with acute necrotizing tonsillitis and Sweet syndrome. A 33-year-old female presented with fever, bilateral cervical lymphadenopathy, tonsillar enlargements with ulcerated pus-filled lesions on the right tonsil, and multiple pseudovesicular, mammillated, edematous plaques on her neck, face, and extremities. Syphilis serology was positive and a skin biopsy demonstrated a neutrophil-rich dermatitis characteristic of Sweet syndrome. The association of Treponema pallidum infection with Sweet syndrome may be a coincidence; nevertheless, our case serves as a reminder that secondary syphilis should remain in the differential diagnosis of the acute febrile neutrophilic dermatosis.